Canons 983; 1388: The Seal of Confession - Daly, Brendan (Roman Replies and CLSA Advisory Opinions 2018, 2018)
The Australian Royal Commission into Institutional Response to Child Abusers commended “no excuse, protection, nor privilege” should apply for priests who failed to convey information about child abuse to the police because it was reported during confession. He Commission hat heard evidence of paedophile priests who received absolution and continued to abuse minors. The Commission also heard of child victims telling confessors they were sexually abused yet nothing was done to stop the abuser. “How does the seal of confession apply to a paedophile penitent who confesses the sin and a child penitent who reveals the abuse in the context of confession?